2000
DOI: 10.1523/jneurosci.20-17-06612.2000
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Activation Evoked by Infrequent Target and Novel Stimuli in a Visual Target Detection Task: An Event-Related Functional Magnetic Resonance Imaging Study

Abstract: An event-related functional magnetic resonance imaging study of prefrontal cortex was conducted during which subjects performed a visual "oddball" target detection task. Exemplars of three stimulus categories were presented at a rate of one per 1.5 sec for 10 runs, each consisting of 132 trials. Standards were color squares of varying sizes that were presented on ϳ92% of trials. Targets were color circles of varying sizes presented irregularly on ϳ4% of trials. Novels were pictures of everyday objects that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
139
2
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 210 publications
(171 citation statements)
references
References 27 publications
29
139
2
1
Order By: Relevance
“…The dorsal frontoparietal regions engaged by attentional targets in the present study are consistent with those reported in previous oddball tasks [4,8,9,25,35,49]. Furthermore, we show here that these dorsal regions respond to task-relevant oddball stimuli similarly despite variations in their emotional properties.…”
Section: Dorsal Regionssupporting
confidence: 92%
See 1 more Smart Citation
“…The dorsal frontoparietal regions engaged by attentional targets in the present study are consistent with those reported in previous oddball tasks [4,8,9,25,35,49]. Furthermore, we show here that these dorsal regions respond to task-relevant oddball stimuli similarly despite variations in their emotional properties.…”
Section: Dorsal Regionssupporting
confidence: 92%
“…Finally, we test whether the oddball response in dorsal brain regions is invariant to emotional content. Because dorsal frontoparietal cortex is consistently activated in oddball tasks that have used a variety of target stimuli [8,9,25,35,49], we expect to see similar activity in these regions across the two experimental groups.…”
Section: Introductionmentioning
confidence: 98%
“…Indeed, elegant cellular recording studies in primates indicate that information induced by changes in frontal activation during a matching-to-sample task is shunted to inferotemporal structures that index task context updating for future stimulus presentations (Desimone et al, 1995). Thus, it is reasonable to suppose that P3a and P3b generation stems from frontal and temporal/parietal activations (Ebmeier et al, 1995;Kirino et al, 2000).…”
Section: Neural Origins Of P3a and P3bmentioning
confidence: 99%
“…Polich and Comerchero (2003) and novel stimuli, which is linked to frontal lobe activity. The P3b is related to a controlled cognitive attentional process that is tied to the stimulus evaluation process, which is linked to temporal/parietal areas (Kirino et al 2000;Polich 2007). …”
Section: Erps For Inhibition Between 200 and 400 Msmentioning
confidence: 99%